Sistem Informasi Geografis (SIG) Titik CCTV Di Kota Jambi Berbasis Web - Jupri, Jupri; Assegaff , Setiawan (Jurnal Manajemen Sistem Informasi, 2022)
Requests for information regarding Closed Circuit Television (CCTV) in public areas by the people of Jambi City through the complaint channel, are increasingly being received by the Jambi City Communications and Information Office. The installation of Closed Circuit Television (CCTV) in public areas in Jambi City is one of the service innovations for the community in order to strengthen law enforcement, public order and public convenience and at the same time realize the Jambi City Government's Smart City program. CCTV installations in Jambi City have been carried out in various areas of Jambi City such as in various parking areas in government offices, at crossroads, and red lights. Even private business actors also support the installation of CCTV in their respective business areas. Advances in GIS technology can be applied to mapping the distribution of CCTV points in the city of Jambi to help collect information on the distribution of CCTV points in various public areas of Jambi City electronically so that they can improve excellent service for the community in the field of security and public comfort both for business actors and for visitors who came to the city of Jambi. So the final result of this research is the proposed design of a Web-Based Geographic Information System (GIS) application for CCTV Point in Jambi City. The system development method used is Prototype using Use Case Diagram modeling tools, Activity Diagrams, and Class Diagrams. This research is expected to provide complete information about the distribution of CCTV points in the Jambi City area, and become the initial foundation for integrating all CCTV management in Jambi City.